Actinobacillus succinogenes: Advances on succinic acid production and prospects for development of integrated biorefineries - Pateraki, Chrysanthi; Patsalou, Maria; Vlysidis, Anestis; Kopsahelis, Nikolaos; Webb, Colin; Koutinas, Apostolis A.; Koutinas, Michalis (My University, 2016)
Actinobacillus succinogenes is a wild-type bacterial strain, isolated from bovine rumen, known as one of the most efficient natural producers of succinic acid. Herein, the factors contributing to the fermentative production of succinic acid by A. succinogenes are reviewed with particular focus on raw materials, culture conditions, significance of carbon dioxide availability and downstream separation and purification. The metabolic potential of this strain is evaluated through discussion of the pathways involved in succinic acid production, genome analysis as well as the development of A. succinogenes mutants. The review also addresses the importance of by-product formation during fermentation that constitutes an important aspect regulating succinic acid production by A. succinogenes. The prospect of integrating succinic acid production in future biorefineries is assessed.
Keywords: Actinobacillus succinogenes; Bioconversion; Downstream processing; Integrated biorefineries; Product inhibition; Renewable resources